Influence of Perceived Bullying on Psychological Well-Being of Nurses - Ata, Zainab Mahmoud; Mohammed, Qahtan Qasim (Journal of Science in Medicine and Life, 2024)
Background and objectives: Workplace bullying (WPB) is becoming an increasingly prevalent issue in the healthcare profession, and it has an apparent effect on the psychological well-being of nurses. We conducted a study to assess the perceived levels of bullying and psychological well-being among nurses, and to determine the influence of bullying on their psychological well-being. Methodology: A non-probability (purposive) sample of 250 nurses from the Baqubah and AL-Batool teaching hospitals in Diyala city participated in this descriptive, correlational study. A self-reported questionnaire was used to collect the data. We used the Statistical Package for Social Sciences (SPSS), version 26.0, to analyze and interpret the data. Result: The results indicate that nurses perceive a moderate level of bullying, as reported among 70.6% of them (M±SD= 57.96±12.139), and 17.2% of them perceive a high level of bullying. 89.4% of nurses reported having a moderate psychological well-being, with a mean score of 75.57. Conclusion: This study reveals that nurses experience a significant amount of bullying in their work environment, ranging from moderate to high levels. Despite the prevalence of bullying, most nurses have a moderate level of psychological well-being.